2) -4x – 6(3x + 4) = -4 + 8(1 - x)
2 answers:
Answer:
x=-2
Step-by-step explanation:
-4x – 6(3x + 4) = -4 + 8(1 - x)
Distribute
-4x – 18x -24 = -4 + 8 -8x
Combine like terms
-22x -24 = 4-8x
Add 22x to each side
-22x+22x -24 = 4-8x+22x
-24 =4+14x
Subtract 4 from each side
-24-4 = 4+14x-4
-28 = 14x
Divide each side by 14
-28/14 =14/14
-2 =x
Answer:
x = -2
Step-by-step explanation:
-4x – 6(3x + 4) = -4 + 8(1 - x)
combine like terms
-22x - 24 = -4 + 8 - 8x
Move the variable to the left-hand side and change the sign
-22 + 8 x - 24 =4
-14x = 4 + 24
-14x = 28
Divide both sides of the equation by -14
x = -2
You might be interested in
I don’t think you can do that
45 + 4 makes 49 if that counts
Answer:
FG = 44
EG = 80
Step-by-step explanation:
For FG:
1) 5z - 16 = 3z + 8
2) 5z = 3z + 24
3) 2z = 24
4) z = 12
5) 3(12) + 8 = 44
For EG:
1) 2w + 22 = 4w + 4
2) 2w = 4w - 18
3) -2w = -18
4) w = 9
5) 4(9) + 4 + 2w + 22 = 80
Answer: It is a more efficient way to find x2k than by multiplying x by itself the appropriate number of times.
Step-by-step explanation: Please find the attached file for the solution
Answer:
D=340
Step-by-step explanation:
360-180/9
360-20
340